Coherent THz transition radiation for polarization imaging experiments - Siriwan Pakluea (2020)
© 2019 Elsevier B.V. THz radiation is reflected by conducting materials and has the capability to penetrate a wide variety of non-conducting materials. With such abilities, THz radiation has great potential for imaging applications, e.g., screening and inspection for packaged electronics chips and electronics circuit boards. High intensity THz radiation have been produced by the accelerator-based radiation source at the Plasma and Beam Physics Research Facility, Chiang Mai University, Thailand. The coherent THz transition radiation was generated from short electron bunches of around 8 MeV and an Al-foil tilted by 45°. Characterization of the backward transition radiation properties was conducted, including spatial distribution, polarization and radiation spectrum. The THz radiation was then used to create THz images of a print circuit board by reflective THz imaging setup. THz imaging with polarized transition radiation is demonstrated. With selected radiation polarization, reflective THz imaging can be improved.